2020
DOI: 10.1002/jat.4039
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on endocrine disrupting effects of polychlorinated dibenzo‐p‐dioxins using molecular docking simulation

Abstract: Polychlorinated dibenzo-p-dioxins (PCDDs) are hypothesized to exert their toxic effects in wildlife and humans via endocrine disruption. However, very scanty information is available on the underlying molecular interactions that trigger this disruption. In this study, molecular docking simulation was used to predict the susceptibility of 12 nuclear receptors to disruption via PCDD bindings. Findings revealed that androgen (AR and AR an), estrogen (ER α and ER β), glucocorticoid (GR) and thyroid hormone (TR α a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…This results in the presence of a dioxin level higher than the tolerable weekly intake in the environment [ 47 ]. Dioxin inhibits estrogen-receptor-mediated gene transcription and modulates the expression or interact directly with steroid receptors [ 48 ]. TCDD promotes epigenetic transgenerational inheritance of disease and DNA methylation epimutations in sperm.…”
Section: Endocrine-disrupting Chemicals (Edcs) Transgenerational Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in the presence of a dioxin level higher than the tolerable weekly intake in the environment [ 47 ]. Dioxin inhibits estrogen-receptor-mediated gene transcription and modulates the expression or interact directly with steroid receptors [ 48 ]. TCDD promotes epigenetic transgenerational inheritance of disease and DNA methylation epimutations in sperm.…”
Section: Endocrine-disrupting Chemicals (Edcs) Transgenerational Impactmentioning
confidence: 99%
“…PCBs can interact with steroid receptors or modulate their expression. Based on the in silico simulation of molecule interactions, it was concluded that PCBs were able to interfere with the reproductive process [ 48 ]. PCBs decreased the force and amplitude of oviductal motility and some of them also stimulated the synthesis of leukemia inhibitory factor (LIF).…”
Section: Endocrine-disrupting Chemicals (Edcs) Transgenerational Impactmentioning
confidence: 99%
“…It should be realized that the predictions made by endocrine disruptome are not equally reliable for the different protein targets available for testing in the software, as some targets suffer from bias ( Kolšek et al, 2014 ). Endocrine disruptome has been successfully employed for the prediction of endocrine-disrupting potentials of some chemical substances ( Akinola et al, 2021 , Akinola et al, 2021 , Kenda and Dolenc, 2020 , Plošnik et al, 2015 , Usman and Ahmad, 2019 , Wang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we demonstrated the application of the gradient chip for endocrine disruptors (EDs) test on testis cells cultured in our system. EDs accumulate in the human body and interfere with normal homeostatic control, reproduction, and developmental processes [ 22 ]. Especially, it is known that one of the EDs that is frequently used in the manufacture of various plastics, bisphenol-A (BPA), is easily internalized in the body.…”
Section: Introductionmentioning
confidence: 99%